Pengaruh Pengembangan Karir, Kompensasi dan Kepuasan Kerja Terhadap Retensi Karyawan PT. Sunwoo Garment Indonesia di Sukoharjo. - Juwita Muntari Susanti; Sri Hartono; Istiqomah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
The aim of this finding is to see (1) the influence of career development on worker retention. (2) to see the effect of compensation on worker retention. (3) to see the effect of job satisfaction on worker retention. These findings were applied to employees of PT. Sunwoo Garment Indonesia in Sukoharjo. The method is a quantitative method. Where the population is employees who do their work at PT. Sunwoo Garment Indonesia in Sukoharjo. The sample was 100 respondents with a non-probability sampling technique applying the purposive sampling method. The selection techniques include documentation, observation, questionnaires, questionnaires and literature studies. The analysis technique uses multiple linear regression tests, F tests, t tests and R2. Findings (1) Career development has a positive and significant influence on employee retention. (2) Compensation has a positive and significant influence on employee retention. (3) Job satisfaction has a positive and significant influence on employee retention. (4) The coefficient of determination is 46.2%. Where employee retention can be explained from career development, compensation, job satisfaction, there is 46.2%. Then other variables explain other variables outside of these findings.